Intermedial Ecocriticism: The Climate Crisis Through Art and Media - Bruhn, Jørgen; Salmose, Niklas (Lexington Books, 2023)
Intermedial Ecocriticism: The Climate Crisis Through Art and Media provides an extensive understanding of the climate crisis as it is represented in a number of medial forms, including scientific reports, popular science, graphic novels, documentaries, websites, feature films, and advertising. Theoretically, this is the first book that combines two important theories from the humanities: ecocriticism and intermedial studies. The book carefully develops Intermedial Ecocriticism as a method of investigating how climate crisis is represented and communicated through diverse media types. The chapters each include a comparative analysis of two or three specific media products and how they mediate the climate crisis.